Environmental awareness through Indian green literature: an eco-critical reading of Aranyak and The Hungry Tide - Maria, Mahzabeen Alam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.